Otsukaresamadeshita!: A Critical Analysis of Japan's Toxic Work Culture - Widarahhesty, Yusy (WILAYAH: The International Journal of East Asian Studies, 2020)
Japan is known for its excessive work culture and dedication to work, which led the world to view the country as a ‘workaholic’. The ‘white collar heroes’ or locally known as the ‘salary man’ have been credited with boosting the Japanese economy, at the expense of their own lives. Approximately 1,949 work-related deaths and suicide attempts were recorded in 2019, all due to overwork. This paper analyses the Japanese work culture from the biopolitical power relations and discourse theory using an ethnography approach and participant observation methodology.